10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Alcohol-related harm is a global public health priority. To address a gap in the provision of screening, brief intervention and referral for treatment (SBIRT) in front-line healthcare services, a district health organisation based in South Auckland, Aotearoa New Zealand, adapted and implemented a model of SBIRT called the Alcohol ABC Approach within general practices, maternity services, hospital emergency care, an inpatient ward, an outpatient clinic, and the district-wide community smoking cessation service. The Alcohol ABC approach aims to identify hazardous or harmful alcohol use in adult populations through routine, non-targeted assessment, provide brief advice and support to reduce alcohol consumption, refer people to support services where indicated, and prevent alcohol-related harm. A non-experimental, mixed methods, process and outcome evaluation examined the implementation, quality and outcomes of the programme to inform future delivery. Reflexive thematic analysis of semi-structured interviews with consumers (n = 8) and staff (n = 19) explored experiences and perceptions of conversations about alcohol and implementing the Alcohol ABC Approach. Findings highlight how social norms surrounding alcohol shape the acceptability of conversations, while relational practices grounded in whanaungatanga (relationship-building) and manaakitanga (care and respect) enable more meaningful dignity-enhancing engagement. Participants described conversations about alcohol as increasing awareness, supporting behaviour change, and challenging the normalisation of hazardous drinking. However, implicit and explicit biases, particularly ethnic bias, influenced who was asked about alcohol and how these conversations unfolded. Organisational support was essential for building staff skills and confidence to initiate discussions. These findings highlight the importance of equity-focused, culturally safe SBIRT approaches that address power and bias, and centre relationships in clinical encounters. While grounded in the context of Aotearoa New Zealand, this study offers insights for adapting and implementing alcohol harm reduction interventions in diverse settings, particularly those seeking to integrate decolonising and anti-racist principles.